2022
DOI: 10.3390/biomedicines10020384
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic Inactivation of Antibiotic-Resistant and Sensitive Aeromonas hydrophila with Peripheral Pd(II)- vs. Zn(II)-Phthalocyanines

Abstract: The antimicrobial multidrug resistance (AMR) of pathogenic bacteria towards currently used antibiotics has a remarkable impact on the quality and prolongation of human lives. An effective strategy to fight AMR is the method PhotoDynamic Therapy (PDT). PDT is based on a joint action of a photosensitizer, oxygen, and light within a specific spectrum. This results in the generation of singlet oxygen and other reactive oxygen species that can inactivate the pathogenic cells without further regrowth. This study pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 32 publications
(55 reference statements)
0
4
0
Order By: Relevance
“…This modification can also alter their photophysicochemical properties for enhanced singlet oxygen generation. Pcs have, as a result, shown aPDT against fish pathogenic bacteria [37][38][39][40][49][50][51]. For example, Mantareva et al reported the inactivation of Aeromonas hydrophila and Flavobacterium hydatis using Pd(II) and Zn(II)-phthalocyanine complexes (activated using a 665 nm light source with an output power of 100 mW cm −2 , and at a light dose of 50 J•cm −2 for 20 min) [37,40].…”
Section: Use Of Chlorins As Pss Against Fish Bacterial Pathogensmentioning
confidence: 99%
See 1 more Smart Citation
“…This modification can also alter their photophysicochemical properties for enhanced singlet oxygen generation. Pcs have, as a result, shown aPDT against fish pathogenic bacteria [37][38][39][40][49][50][51]. For example, Mantareva et al reported the inactivation of Aeromonas hydrophila and Flavobacterium hydatis using Pd(II) and Zn(II)-phthalocyanine complexes (activated using a 665 nm light source with an output power of 100 mW cm −2 , and at a light dose of 50 J•cm −2 for 20 min) [37,40].…”
Section: Use Of Chlorins As Pss Against Fish Bacterial Pathogensmentioning
confidence: 99%
“…Pcs have, as a result, shown aPDT against fish pathogenic bacteria [37][38][39][40][49][50][51]. For example, Mantareva et al reported the inactivation of Aeromonas hydrophila and Flavobacterium hydatis using Pd(II) and Zn(II)-phthalocyanine complexes (activated using a 665 nm light source with an output power of 100 mW cm −2 , and at a light dose of 50 J•cm −2 for 20 min) [37,40].…”
Section: Use Of Chlorins As Pss Against Fish Bacterial Pathogensmentioning
confidence: 99%
“…Similarly, complete photoinactivation of MDR and sensitive strains of A. hydrophila was achieved after 48 h using tetra-methylpyridiloxy-substituted Zn(II) phthalocyanine (Zn-PcMe) (5 µM) and red light (665 nm; fluence rate 100 mW/cm 2 ; light dose 50 J/cm 2 ) [175]. Interestingly, the Pd(II) analogue (pPdPc) was less efficient, and PDI with 8 µM of pPdPc resulted in a 5.47-log reduction in the sensitive strain, and a 3.32-log decrease for MDR, although the accumulation of pPdPc was very similar between MDR and sensitive strains [175].…”
Section: Aeromonas Hydrophilamentioning
confidence: 99%
“…The photoinactivation demonstrated a complete activity with 8 µM pPdPc for antibiotic-sensitive strain and with 5 µM ZnPcMe for both antibiotic-resistant and sensitive strains. These results suggest that the uptakes and photoinactivation efficacy of the applied phthalocyanines are not related to the drug sensitivity of both strains (for more information, see [ 17 ]). In a study by Ramachandran et al, TiO 2 NPs and TiO 2 conjugated with N-GQDs/TiO 2 NCs were synthetized via microwave-assisted synthesis and two-pot hydrothermal method, respectively.…”
mentioning
confidence: 99%